Rate Equation Modelling of Nonlinear Dynamics in Directly Modulated Multiple Quantum Well Laser Diodes. Issue 1 (1998) - Bennett, Stephen; Snowden, Christopher M.; Iezekiel, Stavros
Abstract : A theoretical (using rate equations) and experimental study of the nonlinear dynamics of a distributed feedback multiple quantum well laser diode is presented. The analysis is performed under direct modulation. Period doubling and period tripling are identified in both the measurements and simulations. Period doubling is found over a wide range of modulation frequencies in the laser. Computational results using rate equations show good agreement with the experimental results.